Intravascular tissue factor pathway--a model for rapid initiation of coagulation within the blood vessel - Engelmann, Bernd; Luther, Thomas; Müller, Ingrid (Thrombosis and haemostasis, 2003)
The loss of blood through vessel wall ruptures is initially prevented by the rapid adhesion of platelets to the subendothelium, and the formation of a thrombus consisting of platelets and different types of leukocytes. Concomitantly, the coagulation process is thought to be activated by vascular wall tissue factor (TF). Here, a new model for the initiation of coagulation is presented, based on unexpected findings on the presence and functional activation of TF within the blood itself. TF was recently found to be stored in the alpha-granules of resting platelets under physiological conditions. Activation by collagen exposes TF on the platelet cell membrane and on platelet derived microvesicles. Adhesive interactions of the TF bearing platelets and microvesicles to neutrophils and monocytes support the functional activation of the blood based TF. The intravascular TF pathway is proposed to play a significant role during hemostasis by enabling the generation of fibrin at the site of the developing thrombus.